Structurally different neuronal nicotinic acetylcholine receptor subtypes purified and characterized using monoclonal antibodies - Whiting, PJ (J Neurosci, 1987)
Acetylcholine receptors that bind nicotine with high affinity but do not bind alpha-bungarotoxin have recently been immunoaffinity purified from brains of chickens and rats (Whiting and Lindstrom, 1986a, b; Whiting and Lindstrom, 1987a). Antisera to these receptors bind to the nicotinic receptors that regulate cation channel opening on chick ciliary ganglion neurons (Stollberg et al., 1986) and rat PC12 cells (Whiting et al., 1987c). Here we report the preparation and characterization of monoclonal antibodies to chicken brain acetylcholine receptors. These monoclonal antibodies are used to identify 2 nicotinic receptor subtypes in the chicken brain. The 2 subtypes have very similar affinities for nicotine and other cholinergic agonists and antagonists. However, they are structurally distinct, having very similar or identical alpha subunits (Mr 49,000), but different beta subunits (Mr 59,000, or for beta' subunit, Mr 75,000). Evidence is presented that suggests that the subunit stoichiometry of these neuronal nicotinic acetylcholine receptors is alpha n = 2 - 3 beta n = 2 - 3. Different levels of receptor subtype expression were detected in embryonic, compared to adult, chicken brain.